Pathogen reduction with amotosalen/UVA reduces platelet refractoriness in a dog platelet transfusion model. Issue 6 (11th July 2019) - Slichter, Sherrill J.; Bailey, S. Lawrence; Gettinger, Irena; Pellham, Esther; Christoffel, Todd; Castro, Grace; Green, Jennifer M.; Stassinopoulos, Adonis
Abstract : Background and objectives: Pathogen reduction of donor platelets with amotosalen/UVA has been shown to effectively inactivate pathogens and also contaminating white blood cells (WBCs). We wanted to determine whether WBC inactivation could also decrease alloimmune refractoriness to donor platelets. Materials and methods: Platelets were prepared from a donor dog's whole blood, and the platelets were either transfused without modification [standard (STD) platelets] or treated with amotosalen/UVA under conditions modelling the amotosalen/UVA Blood System for human platelets (APR) using either 4 or 3 J/cm 2 of UVA exposure. Platelets were transfused weekly from a single donor dog for 8 weeks or until the recipient dog became refractory to their donor's platelets. Antibody samples were drawn weekly and tested against the donor dog's platelets and WBCs (CD8 and B cells). Results: Only 1/7 (14%) dogs that received STD platelets accepted 8 weeks of donor transfusions. Following APR 4 J/cm 2 donor transfusions, 3/9 (33%) recipients accepted their donor's transfusions, but only one recipient remained antibody negative. Following APR 3 J/cm 2 donor transfusions, the same dose as used for human platelet transfusions, 7/10 (70%) recipients accepted their donor's transfusions, but only two remained antibody negative. Conclusion: As a very high percentage of recipient dogs (70%) accepted APR 3 J/cm 2 donor transfusions, these data suggest that preventing alloimmune platelet refractoriness may be another benefit of pathogen reduction using amotosalen/UVA.